Dual B-cell targeting therapy ameliorates autoimmune cholangitis. Issue 132 (October 2022) - Zhang, Weici; Shao, Tihong; Leung, Patrick S.C.; Tsuneyama, Koichi; Heuer, Luke; Young, Howard A.; Ridgway, William M.; Gershwin, M. Eric
Abstract: Objective: The ability to regulate B cell development has long been recognized to have therapeutic potential in a variety of autoimmune diseases. However, despite the presence of a classic autoantibody in primary biliary cholangitis (PBC), B cell depleting therapy and indeed therapy with other biologic agents has been disappointing. Unsuccessful treatment using Rituximab is associated with elevation of B-cell activating factor (BAFF) level. Indeed, therapies for PBC remain directed at modulating bile salt biology, rather than targeting effector pathways. With these data in mind, we proposed that targeting two major stages of B cell development, namely long-lived memory B cells and short-lived peripheral autoreactive plasma cells would have therapeutic potential. Methods: To address this thesis, we administrated anti-BAFF and anti-CD20 monoclonal antibody to ARE-Del mice, a well-characterized murine model of human PBC. We evaluated and compared the therapeutic efficacy of the two agents individually and the combination of anti-BAFF and anti-CD20 in female mice with well-established disease. Results: Our data demonstrate that there was an increased level of B cell depletion that resulted in a significantly more effective clinical and serologic response using the combination of agents as compared with the use of the individual agents. The combination of anti-BAFF and anti-CD20 treatment was more effective in reducing serum levels of antimitochondrial antibody (AMA), total IgM and IgG compared to mice treated with the 2 individual agents. Combination treatment efficiently depleted B cells in the peripheral blood, peritoneal cavity and spleen. Importantly, we identified a unique IgM + FCRL5 + B cell subset which was sensitive to dual B-cell targeting therapy and depletion of this unique population was associated with reduced portal infiltration and bile duct damage. Taken together, our data indicate that dual B cell targeting therapy with anti-BAFF and anti-CD20 not only led to the efficient depletion of B cells both in the peripheral blood and tissues, but also led to significant clinical improvement. These findings highlight the potential application of combination of anti-BAFF and anti-CD20 in treating patients with PBC. However, additional studies in other animal models of PBC should be undertaken before considering human trials in those PBC patients who have incomplete responses to conventional therapy. Highlights: We administrated anti-BAFF and anti-CD20 antibody to ARE-Del mice, a well-characterized murine model of human PBC. We evaluated the therapeutic efficacy of the two agents individually and the combination of anti-BAFF and anti-CD20. The combination treatment was more effective in reducing serum levels of autoantibody compared to the individual agents. We identified a unique IgM  +  FCRL5 + B cell subset which was sensitive to dual B-cell targeting therapy. Depletion of IgM  +  FCRL5 + B cell subset was associated with reduced portal infiltration and bile duct damage.